Konsep Diri Keluarga yang Memiliki Anggota Keluarga Orang dengan Gangguan Jiwa Riwayat Pasung di Kota Blitar - Aprilia Wulan Gupitasari Cahyono (Journal of Ners and Midwifery, 2017)
In Indonesia, there are 20.000 to 30.000 people with psychic disruption which restrained. There are 14,3% family or about 237 from 1655 families had a member with heavy psychic disruption restrained. The purpose of the research is to identify self concept of family member with psychological disorder restrained history. Population in this research are 30 families which had member with psychological disorder restrained history in Blitar town. The sample size in this research is 30 people using total sampling method. Data collected was conducted by questionnaire. Data collected was done on 28 march - 10 may 2016. Result of the research showed that 73,1% (19 families) have positive self concept, then 26,9% (7 families) have negative self concept. Recommendation from this research is may get specific attention from health worker to give motivation, direction, and give health education to family which have member with psychological disorder and restrained history to keep or increase positive self concept and change the negative self concept be positive especially in role component and personal identity.